Global Chaotic Parameters of Heart Rate Variability During Mental Task - Fontes, Anne M. G. [UNESP]; Garner, David M.; De Abreu, Luiz Carlos; Barbosa, Juliana C. [UNESP]; De Assis, Elisangela Vilar; De Souza, Ana Cecilia A.; Porto, Andrey A. [UNESP]; Valenti, Vitor E. [UNESP] (Wiley-Blackwell, 2016)
We aimed to evaluate the novel chaotic global techniques of heart rate variability (HRV) analysis during a specific autonomic test, the mental arithmetic overload test. These are spectral detrended fluctuation analysis and spectral multi-taper method; in addition to spectral entropy. We analyzed 24 healthy male students-all nonsmokers, aged between 18 and 22 years old. HRV was analyzed in the following periods: control protocol-the 10-min periods before the performance of the task and the 5-min periods during the performance of the test. Following tests for normality; Kruskal-Wallis technique and principal component analysis-it was decided that this type ofmental stimulation did not lead to significant changes in any of the seven combinations of chaotic globals. In conclusion, it was suggested that the time-series be increased to 1000 RR intervals (at least 20 min of electrocardiographic data) and standard nonlinear methods be introduced in combination with spectral factors as a way of increasing the statistical significance. (C) 2015 Wiley Periodicals, Inc.
Keywords: cardiovascular system; autonomic nervous system; mental stimulation; chaos